Interval estimation of the stress-strength reliability for lower record data based on one-parameter exponential distribution using median ranked set sampling and record ranked set sampling - Sorin, Mingkwan; Srisodaphol, Wuttichai (Vol. 151, No. 2 (April 2022) pages 779-791.)
This paper develops interval estimation of stress-strength reliability when data are lower record values from a one-parameter exponential distribution using resampling schemes such as median ranked set sampling (MRSS) and record ranked set sampling (RRSS). For illustrative aims, we inspect the performance of the proposed interval estimation methods, bootstrap, and generalized confidence intervals (CIs) by using a simulation study and real examples. The result indicates that the proposed interval based on a bootstrap percentile (BP) CI and a generalized CI (GC) using MRSS is suitable for the application. -Title page.